2017
DOI: 10.2147/ijn.s144715
|View full text |Cite
|
Sign up to set email alerts
|

A magnetically responsive nanocomposite scaffold combined with Schwann cells promotes sciatic nerve regeneration upon exposure to magnetic field

Abstract: Peripheral nerve repair is still challenging for surgeons. Autologous nerve transplantation is the acknowledged therapy; however, its application is limited by the scarcity of available donor nerves, donor area morbidity, and neuroma formation. Biomaterials for engineering artificial nerves, particularly materials combined with supportive cells, display remarkable promising prospects. Schwann cells (SCs) are the absorbing seeding cells in peripheral nerve engineering repair; however, the attenuated biologic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 45 publications
0
41
0
Order By: Relevance
“…Similarly, shear stress on primary SCs has been shown to reduce the expression of myelin protein genes and promote the proliferation of SCs 14 , 16 . So far, many mechanotransduction pathways have been identified in SCs 13 , and attempts have been made to promote nerve regeneration by mechanically stimulating SCs 19 . Nevertheless, it is far from clear how SCs sense and respond to mechanical signals and consequent effect on nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, shear stress on primary SCs has been shown to reduce the expression of myelin protein genes and promote the proliferation of SCs 14 , 16 . So far, many mechanotransduction pathways have been identified in SCs 13 , and attempts have been made to promote nerve regeneration by mechanically stimulating SCs 19 . Nevertheless, it is far from clear how SCs sense and respond to mechanical signals and consequent effect on nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that neurotrophins derived from Schwann cells can activate specific cell surface receptors, which initiate a series of reactions in cells including neuronal morphology, survival, and function [ 13 ]. Some studies have revealed that it is important for Schwann cells to secrete cytokines such as nerve growth factor (NGF) [ 6 ], epidermal growth factor [ 17 ], brain-derived neurotrophic factor [ 15 ], and basic fibroblast growth factor [ 9 ] in the regeneration process of axotomized peripheral nerve fibers [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The animal experiments were approved by the animal ethics committee of the People's Liberation Army (PLA) General Hospital (approval no 2013-X7-29), and all animal experiments were undertaken in conformity with the Guide for the Care and Use of Laboratory Animals (National Institutes of Health publication no 85-23, revised 1985). 26 A total of 270 New Zealand White rabbits (Animal Center, PLA General Hospital, Beijing), weighing 2.5-3.0 kg, were randomly divided into five groups as shown in Table 1. Ketamine hydrochloride (2 mL, 100 mg) and serotrazine hydrochloride (2 mL, 40 mg) were mixed in a 1:1 ratio as the anesthetic in the experiments.…”
Section: Animal Surgical Proceduresmentioning
confidence: 99%